Qualitative Study on the Effect of External Factors on Financial Literacy and Business Orientation Strategy Capability of SME Entrepreneurs in Indonesia - Cholid Mawardi, Moh.; Kodir Djaelani, Abd. (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
First, this study focuses on SME entrepreneurs in Indonesia: This study will focus more on SME entrepreneurs in Indonesia, which is a group of entrepreneurs who have different challenges and needs from large-scale entrepreneurs. This allows the research to go deeper in analyzing the problems faced by SME entrepreneurs and provide more specific solutions. Second, the Combination of Financial Literacy and Business Orientation Strategy Ability: This study combines two variables, namely Financial Literacy and Business Orientation Strategy Ability, where the two variables are interrelated and affect business performance. In previous research, these variables were often studied separately. Third, focus on external factors: In addition to paying attention to internal factors such as management and leadership skills, this study also pays attention to external factors such as the role of the government and the support of SME entrepreneur associations in improving the Financial Literacy and Business Orientation Strategy Capability of SME entrepreneurs in Indonesia. Fourth, Qualitative approach: This study uses a qualitative approach that allows researchers to more deeply understand the experiences and perceptions of SME entrepreneurs related to Financial Literacy and Business Orientation Strategy Capability. In addition, by using a qualitative approach, researchers can explore various aspects that have not been revealed in previous studies. By focusing on SME entrepreneurs in Indonesia and combining Financial Literacy and Business Orientation Strategy Capability, as well as considering external factors and using a qualitative approach, this research can make a significant contribution in improving understanding and effective solutions to the problems faced by SME entrepreneurs in Indonesia.